Aging and CaMKII alter intracellular Ca2+ transients and heart rhythm in Drosophila melanogaster - Santalla, Manuela (2014)
Aging is associated to disrupted contractility and rhythmicity, among other cardiovascular alterations. Drosophila melanogaster shows a pattern of aging similar to human beings and recapitulates the arrhythmogenic conditions found in the human heart. Moreover, the kinase CaMKII has been characterized as an important regulator of heart function and an arrhythmogenic molecule that participate in Ca2+ handling. Using a genetically engineered expressed Ca2+ indicator, we report changes in cardiac Ca 2+ handling at two different ages. Aging prolonged relaxation, reduced spontaneous heart rate (HR) and increased the occurrence of arrhythmias, ectopic beats and asystoles. Alignment between Drosophila melanogaster and human CaMKII showed a high degree of conservation and indicates that relevant phosphorylation sites in humans are also present in the fruit fly. Inhibition of CaMKII by KN-93 (CaMKII-specific inhibitor), reduced HR without significant changes in other parameters. By contrast, overexpression of CaMKII increased HR and reduced arrhythmias. Moreover, it increased fluorescence amplitude, maximal rate of rise of fluorescence and reduced time to peak fluorescence. These results suggest that CaMKII in Drosophila melanogaster acts directly on heart function and that increasing CaMKII expression levels could be beneficial to improve contractility.